Steric effects in the reductive coupling of CO by mixed-sandwich uranium(III) complexes - Tsoureas, Nikolaos; Summerscales, Owen T.; Cloke, F. Geoffrey N.; Roe, S. Mark (Organometallics, 2013)
The selectivity of the mixed-sandwich U(III) complexes of the type [U(η-C8H6{SiiR3-1,4} 2)(η-CpR′)] (R = Me, iPr; R′ = Me4H, Me5, Me4iPr, Me 4SiMe3, Me4Et) toward the reductive coupling of CO to form uranium-bound oxocarbons has been explored. In this context, the new U(III) mixed-sandwich complexes [U(η-C8H6{Si iPr3-1,4}2)(η-CpMe4TMS)], [U(η-C8H6{SiiPr3-1,4} 2)(η-CpMe4iPr)], [U(η-C8H 6{SiiPr3-1,4}2)(η-Cp Me4Et)], [U(η-C8H6{SiMe3-1,4} 2)(η-Cp*)], and [U(η-C8H 6{SiMe3-1,4}2)(η-CpMe4TMS)] have been prepared and structurally characterized. The reactivity toward CO is dominated by the "global" sterics around the uranium center, while selectivity for oxocarbon formation is largely regulated by the steric bulk of the CpR′ ligand. Accordingly, with excess CO [U(η-C 8H6{SiiPr3-1,4}2)(η- CpMe4TMS)] and [U(η-C8H6{Si iPr3-1,4}2)(η-CpMe4iPr)] show no reactivity, [U(η-C8H6{SiMe3-1,4} 2)(η-CpMe4TMS)] is completely selective for the formation of the ynediolate complex [U(η-C8H 6{SiMe3-1,4}2)(η-CpMe4TMS)] 2(μ-η1:η1-13C 2O2), [U(η-C8H6{SiiPr 3-1,4}2)(η-Cp*)] affords only the deltate complex [U(η-C8H6{SiiPr3-1,4} 2)(η-Cp*)]2(μ-η2: η2-C3O3), and [U(η-C8H 6{SiiPr3-1,4}2)(η-CpMe4H)] gives solely the squarate complex [U(η-C8H6{SiiPr 3-1,4}2)(η-CpMe4H)]2(μ- η2:η2-C4O4). Additionally, the squarate moiety has been removed from the uranium center in the last complex by reaction with Me3SiCl to afford the TMS ester of squaric acid, C4O2(OTMS)2. © 2012 American Chemical Society.